Open Arms. - Kuniholm, J.
The best way to really move prosthetics research forward is to hitch a ride on a real market. If we can find an application for a myoelectric human interface in the 32 billion worldwide video game market, for example, we can tap into a massive reserve of people who might not otherwise get involved in the effort. Any tool they develop could be repurposed for prosthetics, allowing that small market to benefit from the economies of scale that are usually available only to much larger ones. The MyOpen project on the Open Prosthetics site is working on ways to create a product that can serve both a niche and a mass market. MyOpen, an open-hardware signal-processing board that will be compatible with APL's arm, will also serve as a universal controller for video games. We want creative people to get their hands on this device and push it to the limits. We want this device to enhance the experience of playing video games, and in doing so, push prosthetics innovation into the 21st century.
Keywords: Biomedical engineering; Myoelectric human interface; Prosthetic arms